The introduction and operation of standard costing at J&P Coats Ltd., 1925–1961: an institutional interpretation. (2nd September 2019) - McKinstry, Sam; Kininmonth, Kirsten; Mathieson, Ken
ABSTRACT: This study provides a history of the introduction and implementation of standard costing at J&P Coats Ltd, the British-based multinational thread manufacturers, between 1925 and 1961. By 1896, the firm had centralised sales and marketing, strategic and treasury management in its head office in Glasgow. The introduction of standard costing was intended to bring financial discipline within each of its home and overseas mills, to add to the central discipline and control which already existed across the company, as well as to facilitate some aspects of central accounting in Glasgow. The study ends in 1961, the year the company merged with Patons and Baldwins, another UK-based textile firm. As a theoretical lens, our history uses institutional theory, as it affects an understanding of the implementation and operation of new management accounting systems. In particular, we explore the concept that the development and use of new accounting systems may well be conditioned by both external and internal 'institutions', or 'ways of doing things'. The Coats study responds to the call for longitudinal analyses of management accounting innovation from an institutional point of view. It shows how institutional factors affected the implementation and use of standard costing within the firm, operating through human actors and changing organisational structures. In addition, the study adds to what is known about the history and chronology of the development of standard costing in the UK, pointing out similarities and differences between what happened at Coats and other adopters. It underscores that what is known about the installation and usage of costing systems would benefit from an understanding of the institutional factors involved.